Democratic Principal Leadership and Its Impact on Educational Quality Improvement - Asna Lutfiani; Junaidah; Ilhami (Journal of Educational Management Research, 2026)
This study aims to describe and analyze the implementation of a democratic leadership style by a school principal in improving educational quality. A qualitative approach with a descriptive method was employed to explore leadership practices within the school context. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and educational staff. Data analysis was conducted through data reduction, data display, and conclusion drawing to ensure systematic interpretation. The findings reveal that the principal implemented democratic leadership by actively involving teachers in decision-making processes, fostering open communication, distributing responsibilities proportionally, and providing trust and recognition for teacher performance. These practices contributed to the improvement of educational quality, reflected in enhanced instructional processes, increased teacher motivation and professionalism, and the development of a collaborative and quality-oriented school culture. The study implies that democratic leadership serves as an effective strategic approach for strengthening educational quality, particularly in schools facing resource limitations.